Association Between Urinary Glyphosate Concentrations and Chronic Obstructive Pulmonary Disease in USA Participants: Evidence from NHANES 2013–2018 - Shi Y; Pu S; Huang N; Wang Y (International Journal of COPD)
Yushan Shi,1,2 Shuangshuang Pu,1 Ning Huang,1 Yan Wang1,3 1Department of Laboratory, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of China; 2Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of China; 3Department of Respiratory and Critical Care, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People’s Republic of ChinaCorrespondence: Ning Huang, Department of Laboratory, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250000, People’s Republic of China, Email amanda678@sina.com Yan Wang, Department of Respiratory and Critical Care, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, 250000, People’s Republic of China, Email yan02356@163.comBackground: Glyphosate has raised health concerns due to its widespread detection in environment and human tissues. Limited evidence exists found in the association between urinary glyphosate concentrations and chronic obstructive pulmonary disease.Methods: Analyzing data from 2588 participants, we applied survey-weighted logistic regression models and cubic spline techniques to quantify link between urinary glyphosate concentrations and prevalence of COPD. Further subgroup and sensitivity analyses were also conducted.Results: Study revealed a significant association between higher urinary glyphosate concentrations that increased risk of COPD. In fully adjusted models, a one-unit increase in natural logarithm of urinary glyphosate was associated with a 35% increased risk of COPD (OR, 1.35, 95% CI, 1.01– 1.82, P=0.043). Subgroup analyses showed consistent associations across different demographic groups with a pronounced association in current smokers and females. Sensitivity analyses and exclusion of participants with chronic kidney disease reinforced the robustness of the findings.Conclusion: Findings provide evidence of a positive association between urinary glyphosate concentrations and prevalence of COPD in a representative sample of the adult population at the United States of America. Further studies are needed to investigate the influence of factors and other environmental pollutants on COPD.Keywords: chronic obstructive pulmonary disease, glyphosate, herbicide, national health and nutrition examination survey, urinary concentrations